A scientometric study on quantitative microbial risk assessment in water quality analysis across 6 years (2016–2021). (25th January 2022) - Nyika, Joan; Dinka, Megersa
Abstract: Water contamination by microbes is a growing environmental challenge that has exacerbated the apparent scarcity of safe drinking water. To alleviate this challenge, it is important to screen water for pathogens to reduce the risk of contracting waterborne diseases among consumers. The use of the quantitative microbial risk assessment (QMRA) tool to approximate illness possibility from exposure to microorganisms using dose–response models between pathogens and their associated health impacts is, therefore, recommended. The aim of this study was to explore the use of QMRA in water quality assessment using a scientometric approach and data sourced from the Web of Science (WoS) database for the period between 2016 and 2021. Articles were searched in the WoS databases before downloading the content for a bibliometric analysis using the VOSviewer software. Additionally, Microsoft Excel was used to analyze the inter-relationships of the searched results. Journal articles had the highest results from the searched query at 90.6% compared to other forms of output. High-impact journals such as the Science of the Total Environment and Water Research had the highest number of publications at 11.056 and 7.5%, respectively. Keyword analysis showed the multidisciplinary nature of the search query based on the clustered themes. The USA and China showed greater publication output with a total of 51.7% of total publications compared to developing countries due to their high research potential and extensive collaborative networks. A similar trend was evident in the institutional analysis with the University of California, USA, and the Chinese Academy of Sciences being the highest research contributors with 8% of the searched output. The study highlighted the need to extend research inputs to developing countries of Africa and Asia to improve their research and development capacity, productivity and share knowledge on QMRA in water quality assessment. HIGHLIGHTS: It is one of a kind of bibliometric study on quantitative microbial risk assessment (QMRA) to the best of my knowledge. It analyzes trends in publication for the past 6 years. It uses only empirical studies to make a quantitative assessment of research growth in QMRA applications in water assessment. It highlights gaps in current research to improve future prospects.